Predictive value of bone destruction and duration of clinical remission for subclinical synovitis in rheumatoid arthritis patients. Issue 4 (July 2015) - Tokai, Nao; Ogasawara, Michihiro; Gorai, Misa; Matsuki, Yuko; Yamada, Yusuke; Murayama, Go; Sugisaki, Nagachika; Nemoto, Takuya; Ando, Seiichiro; Minowa, Kentaro; Kon, Takayuki; Tada, Kurisu; et al.
Abstract: Objectives . Treatment for rheumatoid arthritis (RA) should aim to achieve full remission. The aim of this study was to investigate predictors of persistent subclinical synovitis and whether longer clinical remission is effective in reducing subclinical synovitis. Methods. Forty-four RA patients who achieved DAS28ESR clinical remission for at least 3 months were enrolled in this study and underwent ultrasound examination of 22 joints (bilateral proximal interphalangeal joints, metacarpophalangeal joints, and wrists); bilateral hand X-ray; and blood examination. The severity of synovial effusion, synovial hypertrophy, and blood flow were semi-quantitatively graded from 0 to 3 using gray-scale (GS) and power Doppler (PD) modes. Results. Among patients with DAS28ESR-defined clinical remission, 59.1% (26/44) demonstrated residual synovitis (≥ PD1) in at least one joint. Genant-modified total Sharp score (TSS) demonstrated the highest statistical difference between patients with and without residual subclinical synovitis ( p = 0.0057), and full remission was only observed in patients with low TSS. A nonsignificant trend for decreased residual synovitis with longer sustained clinical remission was also observed ( p = 0.724). Conclusion . Residual synovitis can persist during clinical remission, particularly in patients with progressive bone destruction. Early treatment and longer sustained clinical remission prior to bone destruction are critical for full remission.